Balance sobre salinización y alcalinización en los suelos de la depresión de Baza (Granada) - Español, Español; Español, Español; Español, Español (Ars Pharmaceutica (Internet), 1991)
It has been studied the salt accumulation (salinization and alkalinization) on soils belonging to the Baza Depression ( Granada ). We establish the study in an area where we made fifty seven soil profiles. and we analyzed the potential and actual salinization and alkalinization from the data of the description of those profiles. With the obteined data, we made a soil survey. mapping the different values for actual salinization and alkalinization.